2009
DOI: 10.1073/pnas.0906374106
|View full text |Cite
|
Sign up to set email alerts
|

Shock-synthesized hexagonal diamonds in Younger Dryas boundary sediments

Abstract: The long-standing controversy regarding the late Pleistocene megafaunal extinctions in North America has been invigorated by a hypothesis implicating a cosmic impact at the Ållerød-Younger Dryas boundary or YDB (Ϸ12,900 ؎ 100 cal BP or 10,900 ؎ 100 14 C years). Abrupt ecosystem disruption caused by this event may have triggered the megafaunal extinctions, along with reductions in other animal populations, including humans. The hypothesis remains controversial due to absence of shocked minerals, tektites, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
177
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(191 citation statements)
references
References 37 publications
11
177
2
Order By: Relevance
“…The possible causes of megafaunal extinction at the close of the Pleistocene have been hotly debated, and as the literature on this topic is voluminous, only a brief summary is given here. Three main mechanisms of extinction have been proposed for North America: (1) the human arrival hypothesis (Martin, 1967(Martin, , 1984(Martin, , 2005Haynes, 2013;Sandom et al, 2014, and references therein), wherein humans, newly arrived from Asia, extirpated an unwary North American fauna; (2) the climate change hypothesis, in which the shift from a glacial to an interglacial climate brought about extraordinary changes in ecosystems such that megafaunal species were unable to adapt (Graham and Lundelius, 1984;Meltzer, 2002, 2003 and references therein); and (3) the cosmic catastrophic event hypothesis, where an impact or airburst of an extraterrestrial body (comet or meteor) is thought to have brought about dramatic changes in climate, widespread fires, and demise of human (Clovis culture) and animal (megafauna) populations (Firestone et al, 2007;Kennett et al, 2008Kennett et al, , 2009). Other investigators have pointed out the possibility of a combination of human-caused and climate-related causes of extinction (see discussion in Barnosky et al, 2004).…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
“…The possible causes of megafaunal extinction at the close of the Pleistocene have been hotly debated, and as the literature on this topic is voluminous, only a brief summary is given here. Three main mechanisms of extinction have been proposed for North America: (1) the human arrival hypothesis (Martin, 1967(Martin, , 1984(Martin, , 2005Haynes, 2013;Sandom et al, 2014, and references therein), wherein humans, newly arrived from Asia, extirpated an unwary North American fauna; (2) the climate change hypothesis, in which the shift from a glacial to an interglacial climate brought about extraordinary changes in ecosystems such that megafaunal species were unable to adapt (Graham and Lundelius, 1984;Meltzer, 2002, 2003 and references therein); and (3) the cosmic catastrophic event hypothesis, where an impact or airburst of an extraterrestrial body (comet or meteor) is thought to have brought about dramatic changes in climate, widespread fires, and demise of human (Clovis culture) and animal (megafauna) populations (Firestone et al, 2007;Kennett et al, 2008Kennett et al, , 2009). Other investigators have pointed out the possibility of a combination of human-caused and climate-related causes of extinction (see discussion in Barnosky et al, 2004).…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
“…Following the identification of NDs by Kennett et al (2009aKennett et al ( , 2009b, Daulton et al (2010) attempted to replicate that discovery at two wellknown archaeological sites, Murray Springs, Arizona, and Arlington Canyon, California. Daulton et al (2010) found no YDB NDs and concluded that their findings cast doubt on the presence of YDB NDs, although they pointed out that YDB NDs might "occur inhomogeneously and only in some of the YD-boundary carbons and hence are not observed in our study" (p. 16046).…”
Section: Introductionmentioning
confidence: 99%
“…Its formation was attributed to shock-induced transformation of graphite within the meteorite upon impact with Earth, and its occurrence was used as an indicator of shock [1][2][3] . It has since been reported from several meteorites as well as from terrestrial sediments and has been attributed to asteroidal impacts, both extraterrestrial and on Earth [4][5][6][7] .…”
mentioning
confidence: 97%
“…1a,b) or match those of graphite, but well-resolved X-ray reflections for lonsdaleite have not been reported. Selectedarea electron diffraction (SAED), Raman, electron energyloss spectroscopy (EELS) and high-resolution transmission electron microscopy have also been used for identification of lonsdaleite [4][5][6][7]14,15,18,23,24 ; however, interpretation of data is ambiguous (Supplementary Note 1). In spite of the many diffraction and spectroscopic studies, unambiguous data that prove the existence of lonsdaleite as a distinct material have not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation